Enhancing Students’ Critical Thinking through NASA Science as Interactive Multimedia in Learning Solar System - Nurul Azizah Al Mar'ati; Eka Cahya Prima; Agus Fany Chandra Wijaya (Journal of Science Learning, 2021)
Science and technology advancement in the 21st Century requires several life skills that everyone must learn; critical thinking is one of them. Critical thinking is often defined as a process of metacognition that increases the chances of solving a problem. This research attempted to implement NASA Science as Interactive Multimedia to enhance students' critical thinking in learning Solar System. Interactive Multimedia is student-centered, allowing students to play an active role in learning to promote students' critical thinking skills. This study used a pre-experimental method with one group pretest-posttest design. The sampling used was convenience sampling, which participated in 42 7th grade students of a private school in Bandung. The Objective Test was used as a research instrument for both pretest and posttest. These test items were designed according to Facione's indicators of Critical Thinking Skills. Based on the analysis result, the value of g is 0.48. According to the Wilcoxon test, the hypothesis in this research is accepted. The value of Asymp. sig. (2-tailed) is 0.00, with a sig. α = 0.05. Thus, this research shows that: There is an enhancement of students' critical thinking after using NASA Science in learning Solar System.